2005
DOI: 10.1103/physrevc.72.024906
|View full text |Cite
|
Sign up to set email alerts
|

Charm elliptic flow in relativistic heavy-ion collisions

Abstract: Charm elliptic flow in heavy-ion collisions at the Relativistic Heavy Ion Collider is studied in a multiphase transport model. Assuming that the cross section for charm quark scattering with other light quarks is the same as that between light quarks, we find that both charm and light quark elliptic flows are sensitive to the value of the cross section. Compared to that of light quarks, the elliptic flow of charm quarks is smaller at low transverse momentum but approaches comparable values at high transverse m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 65 publications
3
96
0
Order By: Relevance
“…Although it had been expected that the R AA of heavy flavor is less suppressed and its elliptic flow is smaller as compared to the corresponding quantities for light hadrons, the experimental data show that the suppression of heavy-flavor hadrons at high transverse momentum and its elliptic flow v 2 are comparable to those of light hadrons [6,7]. This is a puzzle for heavy-flavor production and dynamics in relativistic heavy-ion collisions as pointed out by many groups [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For recent reviews we refer the reader to Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Although it had been expected that the R AA of heavy flavor is less suppressed and its elliptic flow is smaller as compared to the corresponding quantities for light hadrons, the experimental data show that the suppression of heavy-flavor hadrons at high transverse momentum and its elliptic flow v 2 are comparable to those of light hadrons [6,7]. This is a puzzle for heavy-flavor production and dynamics in relativistic heavy-ion collisions as pointed out by many groups [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. For recent reviews we refer the reader to Refs.…”
Section: Introductionmentioning
confidence: 99%
“…By using parton scattering cross sections of 6−10 mb, the AMPT model with string melting was able to reproduce both the centrality and transverse momentum (below 2 GeV/c) dependence of the elliptic flow [10] and pion interferometry [22] measured in Au + Au collisions at √ s = 130A GeV at RHIC [37,38]. It has also been used for studying the kaon interferometry [39] and charm flow [40] in these collisions. We note that these parton cross sections are significantly smaller than that needed to reproduce the parton elliptic flow from the hydrodynamic model [41].…”
Section: The Ampt Modelmentioning
confidence: 99%
“…To explain the observed small value of R e AA or large suppression of heavy meson production in relativistic heavy ion collisions, other mechanisms for energy loss of heavy quarks in quark-gluon plasma have been proposed [5][6][7][8][9][10]. Also, it was suggested that the enhancement of charmed baryon production over charmed meson production, i.e., the c /D 0 ratio, would suppress the R e AA of the electrons from heavy mesons [11,12].…”
Section: Introductionmentioning
confidence: 99%